TAJIKISTAN’S ENERGY PROJECTS: PAST, PRESENT, AND FUTURE - PETROV, Gennadi (CENTRAL ASIA AND THE CAUCASUS, 2004)
The first state diesel station with a capacity of 78 kW went into operation in Dushanbe, the republic’s capital, in 1926. And the first hydropower station, Varzobskaia-1, not far from Dushanbe, with a capacity of 7.15 MW was built in 1937. The building of power stations in Tajikistan continued even during the years of the Great Patriotic War (1941-1945), and after it was over, they were erected at an even faster rate. For example, in 1941 the first line of the Khorogskaia hydropower plant in Pamir, the republic’s highest mountainous and most inaccessible region, went into operation, followed in 1945 by the second line. What is more, in the 1930s, intensive study of the republic’s energy resources began, while plan-ning and surveying work was organized for building new facilities. It was carried out on a planned and systematic basis using world experience. In 1949-1950, the first energy program was developed, which took into account the agricultural proclivity of Tajikistan’s economy,1 thus giving it the name of “Electrification of Agriculture.” It envisaged building 956 hydropower plants, with a unitary capacity of 50 to 3,000 kW, 555 of which were to be built in the republic’s most economically developed north, 328 in the central regions, and 73 in sparsely populated and economically underdeveloped Pamir. Their total capacity amounted to 500 MW. This was when specialists understood that only hydropower resources could form the foundation of the republic’s energy development. Their supplies are several times higher than the republic’s own needs, while the country has essentially no industrial deposits of oil and gas, and it is very unprofitable to devel-op the nation’s coal fields.2